Seismic Catalogue for Hengill 2017-2022: Handpicked earthquakes - Reykjavík Energy (Iceland) (Zenodo, 2024)
Earthquake catalogue from the Hengill high-temperature geothermal area, SW Iceland, 2017-2022: Manually refined earthquakes. Iceland GeoSurvey (https://isor.is/) operates a local seismic network in the Hengill area (https://www.fdsn.org/networks/detail/OR/) for ON Power (https://www.on.is/), including streaming of real time data, automatic processing and manual refining of earthquake locations. The purpose of the network is to monitor ON Power’s geothermal operations and natural geothermal activity. All waveform data and earthquake locations made with the seismic network are owned by ON Power. The network is complemented with nearby stations from the SIL national seismic network of the Icelandic Meteorological Office (https://www.vedur.is/). For the purpose of the study “Scattering and absorption imaging of the Hengill high-temperature geothermal area, southwest Iceland” by Napolitano et al., ON Power shares earthquake locations of ML > 0.5 between latitude: 64.02°N - 64.15°N and longitude: 21.1°W - 21.4°W. The earthquake catalogue consists of 2240 events from 2017-2022. ÍSOR manually refined both P and S phases for all 2240 events in the catalogue used for the attenuation tomography. The initial automatic SeisComP picks were generated using the SIL velocity model (Bjarnason et al., 1993), with a constant Vp/Vs ratio of 1.78.